The Effect of Using Interactive Learning Media on Science Learning Outcomes of Class IV Students at SD Negeri 136 Palembang - Resilita, Resilita; Hakim, Lukman; Riyanti, Henni (CV. Rayyan Dwi Bharata, 2024)
This research aims to determine whether there is an influence of the use of interactive learning media on the science learning outcomes of class VI students at SD Negeri 136 Palembang. This research is a quantitative type using the True Experimental type of experimental research method with a Matching Pretest – Posttest Comparison Group Design. The population of this study were all fourth grade students at SD Negeri 136 Palembang. The sample for this research was students in class IV.A and IV.B with a total of 43 students. The sample selection technique used was simple random sampling. Data collection techniques in this research are observation and tests. Data analysis used the Independent sample T-test. The results of this research show that the average posttest learning outcome score for the experimental class is 78.18 and the control class is 67.62. The results of the t-test calculation of learning outcomes obtained t_count= 2.460 ≥ t_tabel= 1.6829 with a significance level = 0.05. Based on the research results, it can be concluded that there is a significant influence of the use of interactive learning media on the science learning outcomes of class IV students at SD Negeri 136 Palembang.